Associations between Antenatal Syphilis Test Results and Adverse Pregnancy Outcomes in Western Kenya - Laktabai, Jeremiah; Mobley, Victoria L.; Prudhomme-O’Meara, Wendy; Taylor, Steve M. (The American journal of tropical medicine and hygiene, 2022)
Maternal syphilis remains a major contributor to poor pregnancy outcomes. Syphilis point-of-care (POC) tests are now used for pregnancy screening; the effect of screening on outcomes is unclear. We enrolled women presenting to antenatal care (ANC) in a matched cohort study at a single site in Kenya tested by either a syphilis-only or an HIV/syphilis dual POC test. Syphilis POC-positive women (patients) were matched 1:2 with POC-negative women (control subjects) on gravidity, gestational age, and HIV status, and were monitored through delivery. Syphilis serum testing was performed every 8 weeks. Pregnancy outcomes were assessed up to 1 month after delivery and compared using prevalence ratios. A total of 151 women were enrolled (51 patients and 100 control subjects) at a mean of 22 weeks gestation; 24% were HIV positive and 40% were paucigravid. A positive Treponema pallidum hemagglutination test was more common among patients (64.7%) than control subjects (11.1%, P < 0.001). Only two women met the definition for incident syphilis. Pregnancy outcomes were available for 147 women. The prevalence of low birthweight (LBW) was greater among patients (15.2%) than control subjects (5.4%, P = 0.052). Of the 109 women with concordant syphilis POC and Treponema pallidum hemagglutination test results at ANC enrollment, LBW prevalence was significantly greater among test-positive (25%) than test-negative (4.9%) women (adjusted prevalence ratio, 5.84; 95% CI, 1.08–31.5). Despite treatment with penicillin, latent syphilis at ANC enrollment was associated with a more than 5-fold increased risk of LBW. Alternate implementation strategies for syphilis POC testing may be necessary to realize the potential of ANC syphilis screening to improve pregnancy outcomes.